The Ability of Union Policy in Achieving Price Stability After Covid-19 in 6 Countries with the Highest Inflation - Fadlan, Ahmad; Rusiadi, Rusiadi; Sepbrina, Kiky (Proceeding International Conference on Malay Identity, 2024)
During COVID-19 pandemic, most people have minimized activities outside the home including the government's recommendation to stay at home to break the chain of COVID-19 spread. If these phenomena continue, such as the volume of supply, people's purchasing power, as well as the inflation rate which continues to be on a downward trend, it is feared that it can make economic growth negative and have a negative impact on all sectors which will lead the economy towards recession and worse to the point of a global economic crisis. This research approach is associative / quantitative research. In supporting quantitative analysis, the Model, VAR, ARDL Panel and Differential Test are used where this model can explain the reciprocal relationship in the long-term economic variables used as endogenous variables. The data used in this study are secondary data derived from the World Bank (https://data.worldbank.org/) and https://www.ceicdata.com/id. In the panel interest rates are able to be a leading indicator of inflation and exchange rates in Venezuela, Zimbabwe, Sudan, Argentina, Iran and Indonesia, then the 6 Countries with the Highest Inflation should keep interest rates will remain stable. During the COVID-19 pandemic there are significant differences in inflation and exchange rates in the 6 Countries with the Highest Inflation before and during the COVID-19 pandemic.